Physicochemical Equivalence and Quality Assessment of Various Brands of Gastro-Resistant Omeprazole Capsules in the Kumasi Metropolis. (9th November 2022) - Osei, Yaa Asantewaa; Oppong Boakye, Elvis; Bayor, Marcel T.; Akuffo Owusu, Frederick William
Abstract : The proliferation of counterfeit and poor-quality drugs is a major public health problem, especially in developing countries such as Ghana where there are inadequate resources to effectively monitor their prevalence. Most of these drugs, which are counterfeited, are drugs, which are in high demand and will reap huge profits for the unscrupulous people who engage in such activities. The introduction of Omeprazole as one of the first-line therapies in the management of peptic and duodenal ulcers in the treatment guidelines of Ghana has resulted in many generics being introduced onto the market. The pharmaceutical quality of fifteen randomly sampled Omeprazole capsule brands in the Kumasi metropolis was assessed using the innovator brand as a comparator to confirm their suitability for patient use and to provide data for drug regulatory agencies in Ghana concerning poor quality omeprazole brands. All the sampled brands complied with the official specifications for identification with good primary and secondary packaging characteristics. Ninety-four (94%) of the sampled brands passed the uniformity of weight test. All the brands ( n = 16) representing 100% passed the disintegration tests. Sixty percent (60%) of the sampled brands passed the drug content test. Ten brands (66.7%) met the specification for in vitro dissolution test. From f 2 analysis, the dissolution profiles of only five brands (31%) were similar to that of the reference brand which indicated that they could be used interchangeably in clinical practice. Conclusively, ten out of the fifteen sampled brands were of good quality and only five could be used as a substitute for the innovator. Thus, regulatory agencies will need to strengthen their postmarket surveillance to ensure that generic brands of good quality are allowed onto the market.